Masking the Integration of Complementary Shape Cues - Geoly, Andrew; Greene, Ernest (Frontiers in Neuroscience, 2019)
Retinal and cortical mechanisms provide for persistence of visual information across intervals of many hundreds of milliseconds, which supports the integration of partial shape cues. The present experiments displayed unknown shapes in a match recognition task, wherein a target shape was quickly followed by a comparison shape, with the task being to specify whether the comparison shape was the same or different from the target. The target and comparison shapes were displayed as sparse dots that marked boundary locations. The first experiment successively displayed the target shape as two complementary subsets and found that the probability of correct match remained above chance with up to 500 milliseconds of subset separation. The second experiment demonstrated masking of the target by a random pattern of dots when the target and mask were displayed simultaneously, but with much less or no masking when the two were separated by 100 milliseconds. The third experiment displayed the target subsets with 200 milliseconds of separation and found that match recognition was disrupted when the random-dot mask was displayed midway between the two subsets. Much less masking of an intact target was produced with that amount of temporal separation, which suggests that mechanisms for integration of shape cues have a special vulnerability to masking. The third experiment also found very little impairment of match recognition when the mask was displayed simultaneous with one of the subsets. We hypothesize that there is embedding of the subset pattern within